الادارة الالكترونية ودورها في تحسين الخدمة العمومية:دراسة حالة شركة توزيع الكهرباء و الغاز سونلغاز- الاغواط - رزوق أسماء; طويسات مارية; بوجلال أحمد (جامعة عمار ثليجي -الأغواط, 2022)
In order to provide quality and effective public services to reach the satisfaction of citizens, various public administrations and institutions sought to shift from the traditional administration, which was characterized by mediocrity, bureaucracy, excessive paperwork and the complexity of procedures, to electronic management, by taking advantage of developments in the field of information and communication technologies. In order to provide quality services and to establish the principle of transparency, objectivity and speed in providing services to the citizen.